Examining the Role of Religion in Increasing the Quality of Life of Women in the Muslim World in the Tanggulangin, Sidoarjo - Kurniawan, Satunggale (Prosperity: Journal of Society and Empowerment, 2025)
This research aims to investigate the interplay between Islam and women's empowerment, specifically examining how Islamic teachings and interpretations shape the social, economic, and political roles of women in Muslim societies. The primary objective of this study is to determine whether Islam functions as a barrier or a catalyst for women's empowerment in contemporary contexts. By analyzing classical Islamic texts and modern interpretations, the research seeks to uncover how religious discourse aligns with or contradicts principles of gender equality and women's rights. Employing a qualitative methodology, the study utilizes a diverse array of scholarly sources, case studies, and empirical data to explore the complex relationship between Islamic principles and the evolving roles of women. The findings reveal that, although certain traditional interpretations of Islam have been employed to justify gender-based restrictions, there is substantial evidence that progressive contextualized interpretations of Islamic teachings can serve as a powerful advocacy tool for women's empowerment. This study contributes to the larger discourse on religion and gender by presenting a nuanced perspective that neither glorifies nor condemns Islam but instead highlights the significance of interpretation, context, and socio-cultural dynamics in shaping gender roles. Ultimately, the research emphasizes the necessity for inclusive and reformative approaches to Islamic thought that advocate for justice and equality for women.